2020
DOI: 10.1111/ggi.13895
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with health‐related quality of life in community‐dwelling elderly people in China

Abstract: Aim: Few studies have comprehensively evaluated the factors associated with health-related quality of life (HRQOL) in the elderly. The purpose of the study is to identify the factors associated with HRQOL using a comprehensive geriatric assessment of community-dwelling elderly people in Beijing, China. Methods:A cross-sectional survey of 896 community-dwelling elderly people in Beijing was conducted through face-to-face interviews. Data regarding sociodemographic factors, chronic disease (assessed by the Cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…On the other hand, diabetic patients maintaining high level of physical activity and exercise were exhibited better QoL [54]. Finally, CIRS was found associated with QoL in community-dwelling older adults [55], as was polypharmacy [56]. Thus, our findings that the addition of these variables to the multivariable models may blunt the association between CKD and QoL further strengthen their role as important correlates of QoL among older people and suggests that the impact of CKD on QoL may be at least partly mediated by risk factors typically observed among older people.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, diabetic patients maintaining high level of physical activity and exercise were exhibited better QoL [54]. Finally, CIRS was found associated with QoL in community-dwelling older adults [55], as was polypharmacy [56]. Thus, our findings that the addition of these variables to the multivariable models may blunt the association between CKD and QoL further strengthen their role as important correlates of QoL among older people and suggests that the impact of CKD on QoL may be at least partly mediated by risk factors typically observed among older people.…”
Section: Discussionmentioning
confidence: 90%
“…Due to the significance of disability and QOL research intensively investigated possible determinants regarding functional status and QOL, in order to promote prevention and rehabilitation schemes [54][55][56][57][58]. Depending on the socio-cultural context frequently observed determinants of disability and QOL are: social demographics, housing situation, socioeconomical status, psychosocial characteristics (social participation, social support), health behaviour, relevant comorbidities, self-rated health as well as the reciprocal interaction of disability and QOL [20,54,[58][59][60][61][62][63][64][65][66]. Regarding the aforementioned determinants, older age represents a risk factor regarding disability [67,68], while its influence on QOL remains controversial [47,49,69].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Moreover, this study findings align with other studies, which discovered that patients with KOA from North, Central, and South America, Europe, Asia, and Brazil significantly impacted their quality of life. [4,18,[30][31][32] These patients characteristics, such as gender, body weight, physical activity, mental health, pain, non-optimal nutrition, and education, impact their quality of life. The results of this study also corroborate those of a recent study that found KOA is strongly linked to worsening mental health and HRQoL in middle-aged (50 years or old) and older men and women.…”
Section: Discussionmentioning
confidence: 99%